Systematic review: predicting and optimising response to anti‐TNF therapy in Crohn's disease – algorithm for practical management - Ding, N. S.; Hart, A.; De Cruz, P. (Alimentary pharmacology & therapeutics, 2016)
Summary Background Nonresponse and loss of response to anti‐TNF therapies in Crohn's disease represent significant clinical problems for which clear management guidelines are lacking. Aim To review the incidence, mechanisms and predictors of primary nonresponse and secondary loss of response to formulate practical clinical algorithms to guide management. Methods Through a systematic literature review, 503 articles were identified which fit the inclusion criteria. Results Primary nonresponse to anti‐TNF treatment affects 13–40% of patients. Secondary loss of response to anti‐TNF occurs in 23–46% of patients when determined according to dose intensification, and 5–13% of patients when gauged by drug discontinuation rates. Recent evidence suggests that the mechanisms underlying primary nonresponse and secondary loss of response are multifactorial and include disease characteristics (phenotype, location, severity); drug (pharmacokinetic, pharmacodynamic or immunogenicity) and treatment strategy (dosing regimen) related factors. Clinical algorithms that employ therapeutic drug monitoring (using anti‐TNF tough levels and anti‐drug antibody levels) may be used to determine the underlying cause of primary nonresponse and secondary loss of response respectively and guide clinicians as to which patients are most likely to respond to anti‐TNF therapy and help optimise drug therapy for those who are losing response to anti‐TNF therapy. Conclusions Nonresponse or loss of response to anti‐TNF occurs commonly in Crohn's disease. Clinical algorithms utilising therapeutic drug monitoring may establish the mechanisms for treatment failure and help guide the subsequent therapeutic approach.